DESAIN LAYOUT DAN ANALISIS RPM SPIN CASTING PADA PRODUK METAL JIG - Muhammad Rizki Pratama Pratama; Muhammad Yunus; Erwanto Erwanto (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Bangka Belitong is one of the largest tin islands in Indonesia. Indonesia’s tin mininng is nearly 300,000 tons a year, but unfortunately 95% of these products are exported overseas because of the scarce products used in the country. The research aims to design the layout of spin casting casting casts and to get a refined product with optimum rotation. The benefit of this study is to help umkm (small medium-size microendeavor) Kebajig Lure to acquire the most subcutaneous product's surface roughness. The method used in this study, using experimental research methods to sift data derived from crusty testing of the surface and simulated results. The result of this research is that 3 variant layout design was woven layout design variant 1, with a runner's position at tail Angle of 135, The most generous variant. The first of the three rounds, the one with rpm (round per minute) 350, is optimal with a rough surface value of 1.41 µm And for a turn which produces the most subtly roughness of the surface with 450 that has a cohesive surface value of 1.19 µm.